Stem cells in neurology - current perspectives - Chary Ely Marquez Batista (Arquivos de Neuro-Psiquiatria, 2014)
Central nervous system (CNS) restoration is an important clinical challenge and stem cell transplantation has been considered a promising therapeutic option for many neurological diseases. Objective : The present review aims to briefly describe stem cell biology, as well as to outline the clinical application of stem cells in the treatment of diseases of the CNS. Method : Literature review of animal and human clinical experimental trials, using the following key words: “stem cell”, “neurogenesis”, “Parkinson”, “Huntington”, “amyotrophic lateral sclerosis”, “traumatic brain injury”, “spinal cord injury”, “ischemic stroke”, and “demyelinating diseases”. Conclusion : Major recent advances in stem cell research have brought us several steps closer to their effective clinical application, which aims to develop efficient ways of regenerating the damaged CNS.